PENGUJIAN KEPERCAYAAN, KEAMANAN, RISIKO DAN KEMANJURAN DIRI TERHADAP PROSES JUAL-BELI MELALUI E-SHOPPING - , YUSTIAN BANGKIT H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is motivated by the emergence of the phenomenon of online shopping through an online shop or from social networks. This study used Technology Acceptance Model as a theoretical framework, which examines external variables effect on intention to use e-shopping. External variables on this study are trust, security, risk and self-efficacy. Data analysis was performed with the Structural Equation Model (SEM) using AMOS 18. Respondents in this research e-shopping service users in Indonesia. The result of this study showed that (1) security and risk variables have an influence on perceived usefulness, whereas the belief variable does not affect the perceived ease of use, (2) security has a positive effect on trust, (3) self-efficacy has a positive influence on perceived ease of use, (4) perceived ease of use and perceived usefulness positively influence the purchase intention in e-shopping, (5) the variables that affect the perceived usefulness buying interest and purchase intention of consumers.